Digital transformation of healthcare services: Case study on services of verification and issuing orthopedic and medical aids - Gavrilov, Goce; Stojmenovska, Irena; Ma, Tiedong; Trajkovikj, Vladmir (My University, 2021)
Digital transformation is influencing every facet of peoples live, including the individual and collective healthcare. In the healthcare area, digital transformation has a significant role for scientists and practitioners as for in increasing the quality of the healthcare systems. The paper's main objective is to overview the of the impact of digital transformation on some services that offers Health Insurance Fund, especially on the quality of services. People with disabilities and people who need specific aids in particular areas or periods need support or assistance in performing various daily tasks. The utilization of digital transformation in some internal processes can improve the whole service, discard various problems, and positively impact the quality of lives of all citizens. The authors presented a research study based on the process of digital transformation in the National Health Insurance Fund (Healthcare Fund) and data and documents analysis of internal processes. The analysis shows that digital transformation affects positively citizens, (insured people of Healthcare Fund), orthopedic companies, and healthcare facilities when using the services and rights from the healthcare insurance and fulfilling obligations. The example of digital transformation and the results from its, presented in this paper can take from healthcare authorities in decision and health policy making.
Keywords: e-services, healthcare, digital transformation, orthopedic and medical aids